Ghrelin Increases Lymphocytes in Chronic Normobaric Hypoxia - Fariba Mirzaie Bavil; Gisou Mohaddes; Hadi Ebrahimi; Rana Keyhanmanesh; Rafigheh Ghiyasi (Tabriz University of Medical Sciences, 2014)
Purpose: Hypoxia is a condition of decreased availability of oxygen. To adapt hypoxia, some changes in blood cells occur in the body. The aim of this study was to evaluate the effect of ghrelin on different types of blood cell in normobaric hypoxia situation. Methods: Thirty-two animals were divided in 4 groups (n=8): control (C), ghrelin (G), hypoxia (H), and hypoxic animals that received ghrelin (H+G). Hypoxia (11%) was induced by an Environmental Chamber System GO2 Altitude. Animals in ghrelin groups received a subcutaneous injection of ghrelin (150 μg/kg/day) for 14 days. Results: Our results show that ghrelin significantly (p<0.05) increased RBC and Hct levels, whereas it significantly (p<0.05) decreased lymphocytes in the blood. RBC, Hct, Hb concentration, platelet and MCV increased significantly (p<0.05) in hypoxic conditions but lymphocytes, monocytes and Polymorphonuclears did not show any significant changes. Platelets had a significant (p<0.05) decrease in hypoxic conditions and ghrelin administration in hypoxic conditions could increase lymphocyte levels significantly (p<0.05). Conclusion: Effect of ghrelin on blood cells could be related to blood oxygen level. Ghrelin in normal oxygen conditions increases RBC and Hct levels but decreases lymphocytes, whereas in hypoxic conditions, ghrelin increases blood lymphocytes.